Analisis Risiko Rantai Pasok Tempe pada Pabrik Tahu dan Tempe Masmo Denpasar Bali - SIREGAR, YOPY YOLA ARDYNA BR; AMBARAWATI, I GUSTI AGUNG AYU; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Supply Chain Risk Analysis of Tempeh at Pabrik Tahu dan Tempe Masmo Denpasar Bali.  This study aims to identify product flow, financial flow and information flow, analyze the risks that occur and formulate risk mitigation to minimize the risks that occur in the tempe supply chain at Pabrik Tahu dan Tempe Masmo. Identification of flows in the supply chain is carried out by interviewing and observing as well as risk analysis using Supply Chain Operation Reference (SCOR) model mapping. The identified risks are then analyzed using the Failure Mode Effect Analysis (FMEA) to calculate the Risk Priority Number (RPN) which will be used for the formulation of risk mitigation. The results showed that there were 18 risk events and 25 risk agents spread on SCOR mapping. The risk agent with the largest RPN value is the wrong fermentation room temperature with a value of 384 and the risk agent with the lowest RPN value is a calculation error when ordering soybeans to suppliers with a value of 1. There are 3 risk priorities given risk mitigation. There are three risk mitigation formulations, namely: (1) monitoring room temperature using a room thermometer, (2) performing regular machine maintenance, conducting specific training for workers and providing reward and punishment, (3) monitoring the quality of soybeans from suppliers.